Insight into halloysite nanotubes-loaded gellan gum hydrogels for soft tissue engineering applications. (1st May 2017) - Bonifacio, Maria A.; Gentile, Piergiorgio; Ferreira, Ana M.; Cometa, Stefania; De Giglio, Elvira
Highlights: A new tri-component gel based on gellan gum, glycerol and halloysite is proposed. The nanocomposite hydrogel has tuneable mechanical and biocompatible features. The physico-chemical characterization reveals the gel morphology and composition. The developed hydrogel is suitable for soft tissue engineering applications. Abstract: A tri-component hydrogel, based on gellan gum (GG), glycerol (Gly) and halloysite nanotubes (HNT), is proposed in this work for soft tissue engineering applications. The FDA-approved GG polysaccharide has been recently exploited as biomaterial because its biomimetic features. Gly is added as molecular spacer to improve hydrogel viscosity and mechanical properties. HNT incorporation within the hydrogel offers the versatility to improve the GG-Gly biocompatibility with potential incorporation of target biomolecules. In this work, hydrogels with different composition ratios are physically crosslinked for tuning physico-mechanical properties. An accurate physico-chemical characterization is reported. HNT addition leads to a water uptake decrease of 30–35% and tuneable mechanical properties with a compressive Young's modulus ranging between 20 and 75 kPa. Finally, in vitro study with human fibroblasts on GG-Gly hydrogels loaded with 25% HNT offered the higher metabolic activities and cell survival up to 7 days of incubation.